THE WOMEN REPRESENTATION IN DETERGENT PRODUCT PACKAGING DESIGNS - dinda aryani (PAROLE: Journal of Linguistics and Education, 2013)
Gender representation in media often portrays stereotypes such as women  representations  constructed  by  culture  and  society  often portraying   women’s code of conduct. Seeing the issue, the study aims  to  reveal    women    representation  in  detergent  packaging designs  and  its  ideology  behind  it.  The  data  collection  is  in  the form  of  visual  images.  Kress  and  van  Leeuwen’s    (2006)  Social Semiotics  theory  on  Reading  Images    is  applied  to  reveal  women representation.  Meanwhile,  ideology  is  investigated  with  Barthes’ signification  order.  The  results  show  that  the  women  are  mostly represented to be feminine, tender, motherly, mature, independent, warm,  loving,  caring,  beautiful,  attractive,  friendly,  and  happy. The ideology constructed is femininity ideology conveyed through several  ways:  mass  media  codes,  fashion,  color  and  non-verbal codes. (118)Representasi  gender  di  media  sering  memotret  sterotype  seperti representasi  wanita  bentukan  oleh  budaya  dan  masyarakat  yang sering  menggambarkan  etiket  kaum  wanita.  Melihat  isu  ini, penelitian    bertujuan  untuk  mengungkap  representasi  wanita  di desain  kemasan  detergen  dan  ideologi  di  baliknya.    Data dikumpulkan dalam bentuk gambar-gambar. Teori Semiotik Sosial tentang  Membaca  Gambar  oleh  Kress  dan  van  Leeuwen  (2006) digunakan  untuk  mengungkap  representasi  wanita.  Sementara, ideologi  dilacak dengan  menggunakan  teori    ‘significance  order  ‘ oleh  Barthes.  Hasil  penelitian  menunjukkan  bahwa  wanita sebagian besar digambarkan sebagai kaum  yang feminin,  lembut, keibuan,  dewasa,  mandiri,  hangat,  penuh  kasih,  peduli,  cantik, menarik,  ramah,  dan  bahagia.  Ideologi  yang  terbentuk  adalah ideologi  feminitas  yang  disasmpaikan  lewat  beberapa  cara:    sandi mass media, sandi warna dan non-verbal. (114)